2018
DOI: 10.7189/jogh.08.020806
|View full text |Cite
|
Sign up to set email alerts
|

A prospective validation study in South-West Nigeria on caregiver report of childhood pneumonia and antibiotic treatment using Demographic and Health Survey (DHS) and Multiple Indicator Cluster Survey (MICS) questions

Abstract: A prospective validation study in South-West Nigeria on caregiver report of childhood pneumonia and antibiotic treatment using Demographic and Health Survey (DHS) and Multiple Indicator Cluster Survey (MICS) questions Background Childhood pneumonia is the single largest infectious cause of death in children under five worldwide. Demographic and Health Surveys (DHS) and Multiple Indicator Cluster Surveys (MICS) provide health information on care sought for sick children in resource poor settings. Despite not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…A total of 360 children without pneumonia were recruited into the study. This recruitment is detailed in a separate study [17]. 302 children of those without pneumonia were included as a control group having been matched to cases of pneumonia; 168 males and 137 females, age 0-52 months (Mean = 15.9, SD = 13.7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 360 children without pneumonia were recruited into the study. This recruitment is detailed in a separate study [17]. 302 children of those without pneumonia were included as a control group having been matched to cases of pneumonia; 168 males and 137 females, age 0-52 months (Mean = 15.9, SD = 13.7).…”
Section: Resultsmentioning
confidence: 99%
“…This sample may also not entirely represent those normally surveyed by DHS and MICS in the community as they may have different characteristics. There was also some loss to follow up in those recruited and therefore this may have introduced some bias [17]. OPC physicians were aware of the study and referred children to the study physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimation of intervention need may require solely population demographics such as age (e.g., for prevention and health promotion interventions) or may require defining specific illnesses or conditions The latter is more subject to reporting bias [6]. Multiple studies have shown poor association or biases between maternally-reported symptoms and clinical pneumonia [7,8], malaria [9], and diarrhea [10] in children under five. A handful of studies (n=3) showed maternal report of both maternal and newborn birth complications is variable [1113].…”
Section: Resultsmentioning
confidence: 99%